Investigation and Analysis on the Setting of Cross Passage and Auxiliary Passage in Extra-Long Highway Tunnel. (2018) - Zhang, Heng; Sun, Jian-chun; Liu, Xiao-cheng; Tu, Peng
Abstract: In order to meet the construction schedule, operation ventilation, escape and rescue requirements, a large number of auxiliary need to be set up in the construction of extra-long highway tunnels, the design parameters of vertical shaft, inclined shaft and parallel heading, cross passage are analyzed by investigation of the design on extra-long highway tunnels. The results show that parallel heading is usually adopted in tunnel with single hole two-way driving which it can be used as the auxiliary passage of the main tunnel during construction period and ventilation as well as rescue passage during operation period. The tunnel is generally divided into 2 sections by auxiliary passages in 3 5 km tunnels; 2 3 sections in 5 10km tunnels; 3 4 sections in tunnels over 10km. The angle of inclined shaft is mostly in 20° 25° which is usually set larger in actual engineering and the efficiency of construction and transportation is fully taken into account. In practical engineering of shafts longer than 400m, the shaft scheme needs to be studied to ensure the safety and economy of shaft structure.